2018
DOI: 10.1002/cctc.201801417
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance and Stable Silicon Photoanode Modified by Crystalline Ni@ Amorphous Co Core‐Shell Nanoparticles

Abstract: Improving the charge separation and transport efficiency at semiconductor-electrolyte interface is critical for high-performance photoelectrochemical (PEC) water-splitting devices. Here, the core-shell-structured Ni@Co nanoislands were electrodeposited onto the surface of n-type Si photoanode to construct a metal-insulator-semiconductor (MIS) structure. We discover that the high-quality interface in Si/SiO x /Ni MIS structure is more efficient for charge extraction and transfer than Si/SiO x /Co. Owing to a sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Recent reports by our group, and others, have demonstrated that aqueous electrodeposition of transition metals nanoparticles (NPs) on n‐Si is effective to prepare inhomogeneous Si/metal Schottky junctions that can be further employed as stable Si‐based photoanodes without protection layer. This type of photoanode has been reported, so far, for n‐Si/Ni and n‐Si/Co junctions and it has been recently shown that the performance of these systems can be enhanced by using an additional catalytic shell, typically a hydroxide, or a metallic coating, over the NPs. To the best of our knowledge, this phenomenon has never been applied to n‐Si/Fe junctions so far, which we present for the first time in this article.…”
Section: Introductionmentioning
confidence: 87%
“…Recent reports by our group, and others, have demonstrated that aqueous electrodeposition of transition metals nanoparticles (NPs) on n‐Si is effective to prepare inhomogeneous Si/metal Schottky junctions that can be further employed as stable Si‐based photoanodes without protection layer. This type of photoanode has been reported, so far, for n‐Si/Ni and n‐Si/Co junctions and it has been recently shown that the performance of these systems can be enhanced by using an additional catalytic shell, typically a hydroxide, or a metallic coating, over the NPs. To the best of our knowledge, this phenomenon has never been applied to n‐Si/Fe junctions so far, which we present for the first time in this article.…”
Section: Introductionmentioning
confidence: 87%
“…Electrodeposition conveniently allows triggering layer by layer modifications at the cocat level (allowing the generation of core-shell structures) and thus, is expected to quickly lead to progress in the optimization the catalytic aspect of these photoanodes. [77,79,84] In addition, progress will probably arise from studying other important considerations such as cocat geometry, adhesion, and surface distribution. Attention should also be paid to a crucial but often neglected aspect that is the photoanode stability when unbiased.…”
Section: -Concluding Remarksmentioning
confidence: 99%
“…Many insulators have been utilized in silicon‐based MIS photocatalyst systems. These include SiO 2 ,28–41 TiO 2 ,42–47 HfO 2 ,48,49 Al 2 O 3 ,42,50–53 SrTiO 3 ,54 and ZrO 2. 55 Initially, MIS systems were motivated by their ability to improve the chemical stability of semiconductors, but recently many design strategies have been identified to improve the efficiency of these systems.…”
Section: Introductionmentioning
confidence: 99%